1973
DOI: 10.1099/00221287-76-1-85
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginase and Glutaminase Activities of Micro-organisms

Abstract: S U M M A R YL-Asparaginase and L-glutaminase activities were detected in many microorganisms and the distribution of these activities was found to be related to the classification of micro-organisms.Among 464 bacteria, the activities occurred in many Gram-negative bacteria and in a few Gram-positive bacteria. Most members of the family Enterobacteriaceae possessed L-asparaginase. L-Asparaginase and L-glutaminase occurred together in a large proportion of pseudomonads. Among Gram-positive bacteria many strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
193
0
16

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(212 citation statements)
references
References 32 publications
3
193
0
16
Order By: Relevance
“…The change of the indicator color from yellow to pink resulted from the increase in pH due to ammonia release. The ammonia along with L-aspartic acid is formed by the deamination reaction of the substrate L-asparagine by L-asparaginase (Imada et al, 1973 andGulati et al, 1997). Thus, the potential strain was selected on the basis of the appearance of a pink zone around the fungal colonies as well as growth of the organism.…”
Section: Screening Of Fungal Isolates For L-asparaginase Production Umentioning
confidence: 99%
See 1 more Smart Citation
“…The change of the indicator color from yellow to pink resulted from the increase in pH due to ammonia release. The ammonia along with L-aspartic acid is formed by the deamination reaction of the substrate L-asparagine by L-asparaginase (Imada et al, 1973 andGulati et al, 1997). Thus, the potential strain was selected on the basis of the appearance of a pink zone around the fungal colonies as well as growth of the organism.…”
Section: Screening Of Fungal Isolates For L-asparaginase Production Umentioning
confidence: 99%
“…L-asparaginase Assay L-asparaginase activity was measured following the method of Imada et al (1973). This method utilizes the determination of ammonia liberated from Lasparagine in the enzyme reaction by the Nessler's reaction.…”
Section: Crude Enzyme Extractionmentioning
confidence: 99%
“…L-glutaminase was assayed by direct Nesslerization according to Imada et al [13]. The enzymatic reaction mixture contains 1 ml of 1% L-glutamine in citrate-phosphate buffer (pH 7.0) and 1ml of the crude enzyme incubated at 30°C for 1 h. The enzymatic acitivty was stopped by adding 0.5 ml of 1.5 M trichloroacetic acid.…”
Section: L-glutaminase Assaymentioning
confidence: 99%
“…L-glutaminase production by various bacterial genera under submerged culture conditions was extensively studied [12][13][14]. Furthermore, submerged cultures of Verticillium malthousei [13], Aspergillus sojae [15], A. nidulans [16], Tilachlidium humicola [17] and Penicillium notatum [18] had been used for L-glutaminases production. It appears from the documented literature a few reports being intensive, only, on the production of L-glutaminase by Aspergillus oryzae [19], Beauveria sp.…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of strains of Pseudomonas species showed L-asparaginase and L-glutaminase simultaneously. Most members of the Enterobacteriaceae are active for L-asparaginase but not so active for L-glutaminase [33]. While Roberts et al [21] isolated Achromobacteraceae from the soil samples and observed that this family has L-glutaminase and L-asparaginase activity in a ratio of 1.2:1.…”
Section: Bacterial Amidasesmentioning
confidence: 99%